Progression of asymptomatic nephrolithiasis in children: How often should patients receive follow-up ultrasound imaging?. Issue 1 (February 2022) - Jayman, John; Gibbs, Hannah; Mathias, Robert; Epelman, Monica; Ellsworth, Pamela
Summary: Introduction: The natural history of asymptomatic nephrolithiasis (AN) in children is not well defined. Furthermore, there is no guidance on the utility of repeated renal ultrasound evaluations in this same population. Follow-up ultrasound studies are often obtained as frequently as every 6 months. The goal of this study is to assess the follow-up ultrasound interval in the management of these patients. Methods: A retrospective IRB approved chart review was performed for patients seen for non-cysteine AN between 2012 and 2019. AN was defined as patients without obstructive uropathy abdominal, flank pain and/or gross hematuria. Asymptomatic stones were discovered incidentally or after an acute stone event. Patients with pre-existing renal anomalies and the timepoints with stone passage or stone procedure were excluded. Descriptive statistics were used for demographic information. Multiple linear regression was used to analyze risk factors. Statistical significance was set to p < 0.05. Results: Twenty-nine patients had 90 ultrasounds. The average age at diagnosis was 10.8 ± 6.2 years. The average number of ultrasound studies per patient was 3.2 ± 1.7. The median time between follow-up ultrasounds was 5.2 months [IQR 2.8–10.0]. Median follow-up of patients was 10.6 months [IQR 4.9–21.9]. The change in total stone burden occurred at a rate of 0.11 mm/month (CI [-0.06–0.28], p = 0.20, r 2  = 0.42) or 0.66 mm/6 months. Patients with more renal stones had almost a threefold increase in stone burden compared to patients with fewer renal stones (2.98 [CI 1.34–4.62], p=0.001, r 2 =0.33). Patients with a family history of stones had a twofold increase in the size of their largest stone when compared to patients without a family history (1.97 [CI 0.26–3.68], p=0.02, r 2 =0.60. Conclusion: A complex interplay of multiple factors influence the progression of AN in children. Children with a greater number of stones have a higher increase in total stone burden and children with a family history of stones have a faster increase in largest stone size. These patients may require more frequent imaging studies. The small change in stone size over time favors a longer than 6-month interval for many children.